The Impact of Formative Assessment on Classroom Interaction The Case of First Year Students at the Department of English, Mohamed Cherif Messaadia University, Souk-Ahras - BENYOUB Ahlem (My University, 2024)
ABSTRACT This study explores the impact of formative assessment on classroom interaction among first-year LMD students in the department of English at Mohamed Cherif Messadia University of Souk- Ahras. It aims to investigate teachers' awareness and use of formative assessment, as well as the extent to which it affects classroom interaction. Additionally, the study seeks to identify the most effective formative assessment techniques that influence student engagement, and participation Our research employs a mixed-methods approach, combining quantitative data from students’questionnaires with qualitative insights from classroom observation and interview with teachers. The obtained findings highlight that the use of different forms of formative assessment significantly fosters classroom interaction by promoting a supportive, collaborative, and positive learning environment that increases student motivation and engagement. Based on these findings, our hypotheses are confirmed. The more formative assessment is used, the more classroom interaction is enhanced. Oppositely, the less formative assessment is used, the less classroom interaction is enhanced ----------------- الملخص تستكشف هذه الدراسة تاثير التقيييم التكويني على التفاعل الصفي بين طلاب السنة اولى في قسم اللغة الانجليزية بجامعة محمد الشريف مساعدية بسوق اهراس .و يهدف الى التحقق من وعي المعلمين و استخدام التقييم التكويني فضلا عن مدى تاثيره على التفاعل في الفصول الدراسية .بالاضافة الى ذللك تسعى الدراسة الى تحديد تقنيات التقييم التكويني الاكثر فعالية و التي تؤثر على مشاركة الطالب .يستخدم بحثنا منهج متعدد الاساليب يجمع بين البيانات الكمية من استبيان الطلاب و الرؤى النوعية من مراقبة الفصل الدراسي و المقابلة مع المعلمين تسلط النتائج التي تم الحصول عليها الضوء على ان استخدام اشكال مختلفة من التقييم التكويني يعزز بشكل كبير التفاعل في الفصول الدراسية من خلال تعزيز بيئة تعليمية داعمة و تعاونية و ايجابية تزيد من تحفيز الطلاب و مشاركتهم و بناءا على هذه النتائج تم تاكييد فرضياتنا كلما تم استخدام التقييم التكويني بشكل اكبر يتم تعزيز التفاعل في الفصول الدراسية و على العكس من ذلك كلما تم استخدام التقييم التكويني بشكل اقل كلما نقص التفاعل في الفصول الدراسية ----------------- Résumé Cette étude explore l’impact de l’évaluation formative sur l’interaction en classe chez les étudiants de première année du département d’anglais de l’Université Mohamed Cherif Messadia de Souk- Ahras. Il vise à étudier la sensibilisation des enseignants et l’utilisation de l’évaluation formative, ainsi que la mesure dans laquelle elle affecte l’interaction en classe. De plus, l’étude cherche à identifier les techniques d’évaluation formative les plus efficaces qui influencent l’engagement, la participation et les résultats d’apprentissage des élèves. Notre recherche utilise une approche à méthodes mixtes, combinant les données quantitatives des questionnaires des élèves avec des aperçus qualitatifs de l’observation en classe et des entrevues avec les enseignants. Les résultats obtenus montrent que l’utilisation de différentes formes d’évaluation formative favorise considérablement l’interaction en classe en favorisant un environnement d’apprentissage positif, collaboratif et favorable qui augmente la motivation et l’engagement des élèves. Sur la base de ces résultats, nos hypothèses sont confirmées. Plus l’évaluation formative est utilisée, plus l’interaction en classe est améliorée. À l’opposé, moins l’évaluation formative est utilisée, moins l’interaction en classe est améliorée.